SAT0302 Analysis of 9302 patients from the big data international primary sjÖgren syndrome cohort: clinical presentation at diagnosis of european vs non-european patients. (15th June 2017) - Brito-Zerόn, P; Acar-Denizli, N; Zeher, M; Rasmussen, A; Seror, R; Mandl, T; Li, X; Baldini, C; Gottenberg, J-E; Danda, D; Priori, R; Quartuccio, L; et al.
Abstract : Objectives: Baseline characterization of European patients diagnosed with primary Sjögren syndrome (SS) according to the 2002 AE criteria. Methods: The Big Data Sjögren Project was formed in 2014 to take a "high-definition" picture of the main features of primary SS by merging international SS databases. International experts of the EULAR-SS Task Force were invited to participate. By January 2017, the database included 9302 consecutive patients recruited from 21 countries of the 5 continents. Results: A total of 6586 (71%) patients were included from European countries. In comparison with non-European countries, European patients had a higher mean age (54 v 51yrs, p<0.001), higher frequency of men (7% v 5%, p=0.001), dry eyes (94% vs 88%, p<0.001), dry mouth (94% vs 91%, p<0.001), and lower frequency of abnormal ocular (84 vs 86%, p=0.049) and oral (75 vs 81%, p<0.001) tests. Immunologically, European patients had a lower frequency of anti-Ro/La antibodies (69 vs 78%, p<0.001) and a higher frequency of RF (50 vs 47%, p=0.01), low C4 (14 vs 9%, p<0.001) and cryoglobulins (8% vs 3%, p<0.001). Logistic regression identified as independent variables older age (OR 1.02), male gender (OR 2.62), abnormal oral tests (OR 0.26), anti-Ro/La antibodies (OR 0.69), RF (OR 1.76), low C4 (OR 1.97) and cryoglobulins (OR 3.85). Conclusions: European patients are diagnosed at older age, are more frequently men, and presented a lower frequency of anti-Ro/La antibodies and a higher frequency of immunological markers related to mixed cryoglobulinemia. Disclosure of Interest: None declared